Infants Generalize Beliefs Across Individuals - Burnside, Kimberly; Neumann, Cassandra; Poulin-Dubois, Diane (Frontiers in Psychology, 2020)
It has been argued that infants possess a rich, sophisticated theory of mind (ToM) that is only revealed with tasks based on spontaneous responses. A mature (ToM) implies the understanding that mental states are person specific. Previous studies on infants’ understanding of motivational mental states, such as goals and preferences have revealed that, by 9 months of age, infants do not generalize these motivational mental states across agents. However, it remains to be determined if infants also perceive epistemic states as person specific. Therefore, the goal of the present study was to use a switch agent paradigm with the classic false belief violation-of-expectation task. Results revealed that 16-month-old infants attributed true and false beliefs to a naïve agent – they did not perceive beliefs as person specific. These findings indicate that the mechanisms that underlie infants’ implicit attribution of beliefs differ from those assumed for explicit reasoning about beliefs.